The place of Latin America in the strategy of improving the French trade balance the specific case of Chile - Banfo, Marine; Durrmeyer, Sébastien; Inostroza Pino, Luis; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
Since the beginning of the twenty-first century, French economy as been affected by a constant and deeper trade deficit. After the financial crisis of 2009, the economy still experiences difficulties to bounce back in the context of a weakened Europe. On its side, in the early 2000s, the Latin American countries were about to go through a bright economic period. In deed, the region benefited from a rapid economic growth this last decade, with strong economies and reasonable political stability. The region is also counting with new strong economic partners like China and other Pacific Asian countries. In this work the main objective is to evaluate the trade relations between France and Latin America. I will explore the context in which those relations have been developed and their actual intensity. Then I will study the French external trade situation and the new plan the French Ministry of Trade implemented since 2012. Finally, I will develop the case of Chile and its relations with France, identifying the opportunities for both sides. Unfortunately, this specific subject is not documented by a large amount of printed literature. Thereby, this work is mainly based on statistical information published by international or regional organizations, and on transformed data collected from government or international institutions databases.
Vedoucí práce: Sébastien Durrmeyer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses